The Little Book of Bitcoin What You Need to Know That Wall Street Has Already Figured Out - Scaramucci, Anthony (John Wiley & Sons, Incorporated, 2024)
Expert financial guide to understand the technology, potential, and disruptive effects of crypto In The Little Book of Bitcoin, founder and co-managing partner of SkyBridge Capital Anthony Scaramucci delivers a comprehensive guide to understand disruption in the financial industry as a result of the emergence and increasing prominence of digital asset technology. Drawing on his involvement in the SkyBridge Bitcoin Fund which has USD310 million in assets under management, this book runs the gambit from basic concepts all the way to implications of decentralized finance on the financial industry and society as a whole. In this book, readers will learn about: Hashes, blockchains, and mining, and how these three processes sync up like an orchestra to make global participation in crypto possible Bitcoin as digital gold, and its similarities and differences to other cryptocurrencies like Ethereum Trading different cryptocurrencies, both popular and lesser known, through centralized platforms like Binance and decentralized finance (DeFi) platforms like Uniswap Promising technology to facilitate anonymized legitimacy called "zero knowledge proof" and how it works The Little Book of Bitcoin is an essential up-to-date guide to digital assets and associated technologies for all individuals, from hedge fund managers to newcomer retail investors, seeking to understand and prepare for a new world of finance.
Description based upon print version of record
Keywords: Bitcoin; Investments; Cryptocurrencies; Investissements; Cryptomonnaie; cryptocurrencies; Analysis & Trading Strategies; Wealth Management; Finance; BUSINESS & ECONOMICS; Investing; Personal Finance; Investments & Securities